2019
DOI: 10.1681/asn.2018121194
|View full text |Cite
|
Sign up to set email alerts
|

Renal Perfusion during Hemodialysis: Intradialytic Blood Flow Decline and Effects of Dialysate Cooling

Abstract: BackgroundResidual renal function (RRF) confers survival in patients with ESRD but declines after initiating hemodialysis. Previous research shows that dialysate cooling reduces hemodialysis-induced circulatory stress and protects the brain and heart from ischemic injury. Whether hemodialysis-induced circulatory stress affects renal perfusion, and if it can be ameliorated with dialysate cooling to potentially reduce RRF loss, is unknown.MethodsWe used renal computed tomography perfusion imaging to scan 29 pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
46
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(50 citation statements)
references
References 65 publications
2
46
0
1
Order By: Relevance
“…3,82 Although no RCTs have demonstrated that lowering UF rates improves outcomes, biologic plausibility data support a relationship between higher UF rates and end-organ ischemia (heart, brain, liver, gut, kidneys). [83][84][85][86][87][88][89] A critical unanswered question is how to balance the potential risks from higher UF rates with the potential risks from volume overload. 80 In the absence of conclusive data, using one specific UF rate threshold for all patients at all times is likely inappropriate.…”
Section: Intradialytic Hypotension and The Hd Prescriptionmentioning
confidence: 99%
“…3,82 Although no RCTs have demonstrated that lowering UF rates improves outcomes, biologic plausibility data support a relationship between higher UF rates and end-organ ischemia (heart, brain, liver, gut, kidneys). [83][84][85][86][87][88][89] A critical unanswered question is how to balance the potential risks from higher UF rates with the potential risks from volume overload. 80 In the absence of conclusive data, using one specific UF rate threshold for all patients at all times is likely inappropriate.…”
Section: Intradialytic Hypotension and The Hd Prescriptionmentioning
confidence: 99%
“…The ultrafiltration technology used in this study not only salvages blood, but also protects the brain and heart from ischemic injury. 11 After the emergency operation, the patient was transferred to a designated negative pressure isolation unit for individual monitoring. Specific postoperative management strategies should strictly follow the infection precaution guidelines, including maintaining hemodynamic stability, electrolyte balance, punctual hemodialysis, infection control, and other treatment programs.…”
Section: Discussionmentioning
confidence: 99%
“…A statistical interaction suggested for acute kidney injury, and the protective effects deep hypothermia could be attenuated by the prolonged CPB time. 11 Because COVID-19 can cause hypoxia in tissues and organs and the 3-level protection requirements may lead to increased operating times for surgeons, this will prolong the CPB time to aggravate organ damage.…”
Section: Discussionmentioning
confidence: 99%
“…62 Importantly, dialysis has negative effects not only on the perfusion of the heart but also on other organs, such as kidney, gut, liver, and brain, as shown by various imaging techniques of positron emission tomography, computed tomography, and MRI. [63][64][65] Apart from direct organ damage by tissue ischemia, hepatosplanchnic circulatory stress may also induce bacterial translocation, endotoxin release, and the increased release of gut-derived uremic toxins such as indoxyl sulphate into the systemic circulation. [66][67][68][69] The importance of these observations is shown by studies reporting an association between mortality and ultrafiltration rate/volume and change in blood pressure and end-organ ischemic injury.…”
Section: Cardiac and Circulatory Stressmentioning
confidence: 99%